The role of school activities in reducing school dropout phenomenon from the point of view of the principals of public schools in the Deir Ala district in Jordan - Sous, Raeda Hussein Mohammed (Journal of Educational and Psychological Sciences, 2020)
The study aimed at uncovering the role of school activities in reducing school dropout phenomenon from the point of view of the principals of public schools in the Deir Ala district. The researcher used the descriptive approach. In order to achieve the goal of the study, The results showed that the role of school activities in reducing the phenomenon of school dropout with an average of (3.66). The order of the fields ranked in descending order according to the level of fields: Educational field, reached (3.92) (3.40), all of which are rated (high) That the administrative level of creativity of the department heads are high average (3.94), also showed a strong correlation by (0.82). In the light of the results, a number of recommendations and proposals were presented to raise the level of school activities to reduce school dropouts.